Emigration, remittances and the education of children staying behind: Evidence from Tajikistan - Barbara Dietz; Kseniia Gatskova; Artjoms Ivlevs (Institut für Ost- und Südosteuropaforschung (IOS), 2015)
We study the relationship between migration and childrens education in Tajikistan - one of the poorest and most remittance-dependent economies in the world. The analysis of a unique threewave household panel survey reveals that emigration of family members is negatively associated with childrens school attendance. Receiving remittances does not offset this negative effect. Migration of non-parent family members (such as siblings) is particularly detrimental to school attendance, especially among older children and children from less educated households. This supports a conjecture that emigration in Tajikistan has a negative signaling effect on the education of children staying behind.
urn:nbn:de:101:1-201602232282
Keywords: 330; migration; remittances; schooling; Tajikistan